Nilai Keadilan dalam Filsafat Pancasila dan Implementasinya dalam Penegakan Hukum - lutfian ubaidillah; Firman Sulistiyoni; Fendi Setyawan; Dominikus Rato (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Pancasila, as the state ideology, embodies the value of justice, which serves as the foundation for the formation and enforcement of law in Indonesia. However, its implementation still faces various problems, such as legal inequality, low integrity of officials, and weak protection of the poor. The method used is normative legal research with a philosophical and conceptual approach. The results show that Pancasila justice has a unique character because it integrates humanitarian values, balance between rights and obligations, social justice, and moral and spiritual dimensions. Analysis of the theories of justice of Aristotle and John Rawls shows that Pancasila justice is oriented not only toward the distribution of rights and protection of vulnerable groups, but also toward harmony between the interests of individuals and society. This research also found a gap between the values of Pancasila justice and law enforcement practices, which still face issues of unequal legal treatment, corruption, and limited access to justice.